L'età berlusconiana Il centro-destra dai poli alla Casa della Libertà 1994-2001 - Andrea Bussoletti (Premio Tesi di Dottorato, 2015)
This work reconstructs the main national events in the time span between Silvio Berlusconi's arrival on the political scene in 1994 and the start of his second government in 2001. The aim of the volume is to answer some of the main questions which have characterized the public debate in Italy over the past twenty years. Did the transition from the First to the Second Republic really take place? What role did the leader of the party "Forza Italia" play in this process? Does the new political system represent an anomaly compared to Italy's recent history? Answering these questions will make a clear reading of current political affairs easier.